2018
DOI: 10.1007/s10641-018-0816-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards direct evidence of the effects of salmon lice (Lepeophtheirus salmonis Krøyer) on sea trout (Salmo trutta L.) in their natural habitat: proof of concept for a new combination of methods

Abstract: Studies addressing the impact of salmon lice (Lepeophtheirus salmonis Krøyer) on sea trout in their natural habitat are scarce and mostly limited to prophylaxis-based experiments. The main drawbacks with this approach are that lice infestations on control fish are not known and the anti-parasitic treatment is of unknown efficacy and may have unwanted side-effects. We tested an innovative approach where prophylaxis is replaced with artificial infestation of the fish. Twenty-nine sea trout post-smolts were caugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The salmon louse Lepeophtheirus salmonis is a natural parasite in Norwegian waters that feeds on the skin, fat, and mucus of salmonid fish (Pike & Wadsworth 1999). With the industrialization of aquaculture, the numbers of potential hosts have increased, leading to unnaturally high lice infestations on both farmed and wild fish (Finstad et al 2000;Bjorn et al 2001;Heuch & Mo 2001;Heuch et al 2009Heuch et al , 2011Serra-Llinares et al 2018). Salmon lice carry eggs in two eggstrings at the rear of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The salmon louse Lepeophtheirus salmonis is a natural parasite in Norwegian waters that feeds on the skin, fat, and mucus of salmonid fish (Pike & Wadsworth 1999). With the industrialization of aquaculture, the numbers of potential hosts have increased, leading to unnaturally high lice infestations on both farmed and wild fish (Finstad et al 2000;Bjorn et al 2001;Heuch & Mo 2001;Heuch et al 2009Heuch et al , 2011Serra-Llinares et al 2018). Salmon lice carry eggs in two eggstrings at the rear of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other secondary effects associated with the treatment are not expected. Serra-Llinares et al (2018) performed a pilot study to test this new method using wild trout post-smolts (n = 29) caught in bag nets shortly after they entered the sea in Sandnesfjord, southern Norway. The authors concluded that, despite limitations in the statistical power rendered by the study, results indicated consistent trends in behavioural differences between control and artificially infested fish, suggesting that this shift in method (i.e.…”
Section: Introductionmentioning
confidence: 99%